Heart Zone as a measure to influence traffic safety culture: which factors influence culture change? - Milch, Vibeke; Nævestad, Tor-Olav (Traffic Safety Research, 2024)
Measures to influence traffic safety culture in designated areas (e.g. schools) exist in several different countries across the world. The Norwegian traffic safety scheme Heart Zone is a measure that aims to influence the traffic culture within a specific geographical area. The study examines whether four Norwegian schools have managed to establish a Heart Zone traffic safety culture, factors facilitating and impeding the implementation of Heart Zone traffic safety culture and subsequent changes in parents’ traffic safety behavior. The study is based on survey data from four Norwegian schools (n = 220) and qualitative interviews (n = 19). Although the level of implementation varies, results from the interviews and the survey suggest that the schools have established Heart Zone cultures, where large proportions of the parents drop the children off at the recommended drop-off zone, when driving, are attentive to students who come walking/cycling within the Heart Zone and walk or cycle when transporting children within the Heart Zone. The Heart Zone culture is related to changes in parents’ traffic safety behaviors and reductions in dangerous traffic situations. The study identifies specific factors facilitating and impeding traffic culture change, related to enclosed geographical areas like the Heart Zone, developing an analytical model that researchers and future traffic culture measures like this can learn from.